2011
DOI: 10.1371/journal.pone.0024156
|View full text |Cite
|
Sign up to set email alerts
|

Critical Period of Nonpromoter DNA Methylation Acquisition during Prenatal Male Germ Cell Development

Abstract: The prenatal period of germ cell development is a key time of epigenetic programming in the male, a window of development that has been shown to be influenced by maternal factors such as dietary methyl donor supply. DNA methylation occurring outside of promoter regions differs significantly between sperm and somatic tissues and has recently been linked with the regulation of gene expression during development as well as successful germline development. We examined DNA methylation at nonpromoter, intergenic seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…However, in males, DNMT3L was initially detected at 12.5 days after fertilization of the egg, and the levels peaked at 15.5 days and remained upregulated until birth (77)(78)(79). However, the expression of DNMT3L was significantly 79 following birth and was found to be low in mature germ cells (36)(37)(38), suggesting an association between DNMT3L and DNA methylation. In addition, the inactivation of DNMT3L was shown to cause mitotic delays, chromosome synapsis errors and the ceasing of spermatogenesis at the zygotene stage of mitosis, thus inhibiting the maturation of germ cells (46)(47)(48).…”
Section: Dna Methylation and Spermatogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, in males, DNMT3L was initially detected at 12.5 days after fertilization of the egg, and the levels peaked at 15.5 days and remained upregulated until birth (77)(78)(79). However, the expression of DNMT3L was significantly 79 following birth and was found to be low in mature germ cells (36)(37)(38), suggesting an association between DNMT3L and DNA methylation. In addition, the inactivation of DNMT3L was shown to cause mitotic delays, chromosome synapsis errors and the ceasing of spermatogenesis at the zygotene stage of mitosis, thus inhibiting the maturation of germ cells (46)(47)(48).…”
Section: Dna Methylation and Spermatogenesismentioning
confidence: 99%
“…They are considered to differ mechanistically due to inherent differences in their catalytic domains, and it has been suggested that DNMT3a is distributive while DNMT3b is processive (31)(32)(33)(34)(35)(36). The third significant member in the DNMT3 family is DNMT3L, which is considered to be required for the establishment of maternal imprints in oocytes (37)(38)(39)(40)(41), and has also been shown to be expressed during spermatogenesis (37,(42)(43)(44). SAM, as the methyl donor for DNMTs, is formed through the addition of adenosine triphosphate to methionine, which is catalyzed by the methionine adenosyltransferase enzyme.…”
Section: Dna Methylationmentioning
confidence: 99%
“…In this line, one of the main contributions of our study is that we have identified this small but dynamic proportion. It is believed that demethylation and remethylation of repeats is mostly completed before birth 9,[11][12][13] . In the present study, we show that the 5hmC status in repeats keep changing during spermatogenesis even after birth.…”
Section: Article Nature Communications | Doi: 101038/ncomms2995mentioning
confidence: 99%
“…In mice, the majority of methylation in male germ cells is completed before type A SG (SG-A) are formed at 6 days post-partum (dpp), while those at a small number of sites continues to occur until the formation of pachytene SC (pacSC) 10 . Imprinted genes, repetitive sequences and non-promoter intergenic regions complete DNA methylation before birth 9,[11][12][13] . However, little is known about whether and how global DNA methylation changes in germ cells after birth.…”
mentioning
confidence: 99%
“…DNMT3L itself does not possess enzymatic activity but acts as a processive catalyst and cooperates with other DNA methyltransferases (DNMTs) via its C-terminus to promote the de novo methylation of DNA sequences, including retrotransposons, gene bodies and the regulatory sequences of imprinted genes (Bourc'his et al, 2001;Chedin et al, 2002;Hata et al, 2002;Bourc'his and Bestor, 2004;Suetake et al, 2004;Kato et al, 2007;Holz-Schietinger and Reich, 2010;Niles et al, 2011;Smallwood et al, 2011;Van Emburgh and Robertson, 2011;Arand et al, 2012;Kobayashi et al, 2012;Ichiyanagi et al, 2013). In addition, DNMT3L contains a plant homeodomain (PHD)-like domain that can recruit histone modifiers, such as histone deacetylase 1 (HDAC1), or bind to the Nterminus of histone H3 when the lysine 4 of histone H3 is unmethylated (Aapola et al, 2002;Deplus et al, 2002;Jia et al, 2007;Ooi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%